Efeitos sinérgicos da mistura de reagentes no desempenho da flotação catiônica reversa de minério de ferro - Stephânia da Consolação Silva Nogueira (2021)
The mixture of reagents is strategic in the search for more efficient results for ore flotation. When used in the proper process conditions, the interaction of the reagents in the mixture can generate synergistic effects that optimize the performance of these products, in relation to their use individually. Similarly, the effects of mixture or blending can generate antagonistic effects, with one product canceling out or impairing the effect of the other in the process, or simply perform an additive effect with the sum of the contributions of each part, which would naturally be the most expected. Flotation reagents are classified according to their primary functions, such as collectors, frothers and modifying agents. Reverse cationic flotation is the most widely used process for the concentration of low-grade iron ores such as those found in the Brazilian Quadrilátero Ferrífero, where amines are used as collectors and foaming agents, and natural starches are used as modifiers (depressants). The objective of this work was to evaluate the use of mixtures of collecting reagents and depressants in flotation systems, through the identification of synergistic effects of these blends, compared to the use of these reagents individually. Microflotation tests using pure quartz and hematite minerals and bench flotation tests with an iron ore, typical of the Quadrilátero Ferrífero, were carried out to evaluate the use of mixtures of etheramines with different structural characteristics and starches from different botanical sources (corn and cassava). The results clearly showed the occurrence of synergistic effects of the collector mixture on the flotability of quartz (in the absence of starches and in the interaction with cassava starch) and in obtaining the SiO2 content, in the bench flotation tests, as a result. In the evaluation of the depressant mixtures, the 1:1 ratio (50% corn starch and 50% cassava starch) had an antagonistic effect on the flotation of hematite. In the other efficiency parameters tested, the additive effect prevailed.